Insulation of enhancer-promoter communication by a gypsy transposon insert in the Drosophila cut gene: cooperation between Suppressor of Hairy-wing and Modifier of mdg4 proteins. - Gause, M.; Morcillo, P.; Dorsett, D. (Molecular and Cellular Biology, 2001)
The Drosophila mod(mdg4) gene products counteract heterochromatin-mediated silencing of the white gene and help activate genes of the bithorax complex. They also regulate the insulator activity of the gypsy transposon when gypsy inserts between an enhancer and promoter. The Su(Hw) protein is required for gypsy-mediated insulation, and the Mod(mdg4)-67.2 protein binds to Su(Hw). The aim of this study was to determine whether Mod(mdg4)-67.2 is a coinsulator that helps Su(Hw) block enhancers or a facilitator of activation that is inhibited by Su(Hw). Here we provide evidence that Mod(mdg4)-67.2 acts as a coinsulator by showing that some loss-of-function mod(mdg4) mutations decrease enhancer blocking by a gypsy insert in the cut gene. We find that the C terminus of Mod(mdg4)-67.2 binds in vitro to a region of Su(Hw) that is required for insulation, while the N terminus mediates self-association. The N terminus of Mod(mdg4)-67.2 also interacts with the Chip protein, which facilitates activation of cut. Mod(mdg4)-67.2 truncated in the C terminus interferes in a dominant-negative fashion with insulation in cut but does not significantly affect heterochromatin-mediated silencing of white. We infer that multiple contacts between Su(Hw) and a Mod(mdg4)-67.2 multimer are required for insulation. We theorize that Mod(mdg4)-67.2 usually aids gene activation but can also act as a coinsulator by helping Su(Hw) trap facilitators of activation, such as the Chip protein.